The Impact of the Marketing Mix on College Selection: A 7-Parameter Analysis (Jurnal Manajemen Bisnis, 2022)
The technique used in sampling is probability sampling technique, in order to obtain a total sample of 80 students of the Master of Accounting Study Program, Faculty of Economics and Business, Tarumanagara University. The source of data in this study is primary data. The analytical method used is multiple linear regression analysis using SPSS software. Simultaneous test results (Test F) show that Product (X1), Price (X2), Place (X3), Promotion (X4), People (X5), Process (X6), and Physical Evidence (X7) have a positive and significant effect on decision to choose (Y) on students of the Master of Accounting Study Program, Faculty of Economics and Business, Tarumanagara University in Jakarta. The results of the partial test (t test) that have a positive and significant effect on the decision to choose (Y) are the product (X1) and process (X6) variables while the Price (X2), Place (X3), Promotion (X4), People (X5) variables, and Physical Evidence (X7) has no effect and is not significant on the decision to choose (Y) on students of the Master of Accounting Study Program, Faculty of Economics and Business, Tarumanagara University in Jakarta.